Harnessing fluoroacetate dehalogenase for defluorination of fluorocarboxylic acids: in silico and in vitro approach. (October 2019) - Li, Yanwei; Yue, Yue; Zhang, Hongxia; Yang, Zhongyue; Wang, Hui; Tian, Shaixiao; Wang, Jian-bo; Zhang, Qingzhu; Wang, Wenxing
Abstract: Widely distributed fluorocarboxylic acids have aroused worldwide environmental concerns due to its toxicity, persistence, and bioaccumulation. Enzyme-based eco-friendly biodegradation techniques have become increasingly important in treating fluorocarboxylic acids. Here we utilized in silico and in vitro approaches to investigate the defluorination mechanism of fluoroacetate dehalogenase (FAcD) toward monofluoropropionic acids at atomic-level. The experimentally determined k cat and k M for defluorination of 2-fluoropropionic acid are 330 ± 60 min − 1 and 6.12 ± 0.13 mM. The in silico results demonstrated positive/negative correlations between activation barriers and structural parameters ( e.g. distance and angle) under different enzymatic conformations. We also screened computationally and tested in vitro (enzyme assay and kinetic study) the catalytic proficiency of FAcD toward polyfluoropropionic acids and perfluoropropionic acids which are known to be challenging for enzymatic degradation. The results revealed potential degradation activity of FAcD enzyme toward 2, 3, 3, 3-tetrafluoropropionic acids. Our work will initiate the development of a new "integrated approach" for enzyme engineering to degrade environmentally persistent fluorocarboxylic acids. Graphical abstract: Unlabelled Image Highlights: Enzyme FAcD was firstly demonstrated to degrade polyfluorocarboxylic acids. The key for efficient CF bond cleavage lies in the topology of the active site. The defluorination barriers are correlated with enzyme structural parameters.